2020
DOI: 10.1111/ejn.15023
|View full text |Cite
|
Sign up to set email alerts
|

Functional interactions between cannabinoids, omega‐3 fatty acids, and peroxisome proliferator‐activated receptors: Implications for mental health pharmacotherapies

Abstract: Cannabis contains a plethora of phytochemical constituents with diverse neurobiological effects. Cannabidiol (CBD) is the main non-psychotropic component found in cannabis that is capable of modulating mesocorticolimbic DA transmission and may possess therapeutic potential for several neuropsychiatric disorders. Emerging evidence also suggests that, similar to CBD, omega-3 polyunsaturated fatty acids may regulate DA transmission and possess therapeutic potential for similar neuropsychiatric disorders. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 135 publications
(237 reference statements)
0
9
0
Order By: Relevance
“…For example, Murphy and colleagues found that CBD and THC co-administration in adolescent mice prevented deficits in working memory, anxiety, and compulsive-like behaviors [108] (Table 1). Although the mechanisms are not yet fully elucidated, CBD may either antagonize THC effects via negatively modulating an allosteric site of CBRs [109] or interacting with other molecular substrates [101,[110][111][112]. For instance, CBD has been found to exert its therapeutic properties by increasing serum levels of endogenous AEA, potentially through inhibition of the enzyme fatty acid amide hydrolase (FAAH) [113].…”
Section: Therapeutic Perspective: Potential Intervention For Mitigate...mentioning
confidence: 99%
“…For example, Murphy and colleagues found that CBD and THC co-administration in adolescent mice prevented deficits in working memory, anxiety, and compulsive-like behaviors [108] (Table 1). Although the mechanisms are not yet fully elucidated, CBD may either antagonize THC effects via negatively modulating an allosteric site of CBRs [109] or interacting with other molecular substrates [101,[110][111][112]. For instance, CBD has been found to exert its therapeutic properties by increasing serum levels of endogenous AEA, potentially through inhibition of the enzyme fatty acid amide hydrolase (FAAH) [113].…”
Section: Therapeutic Perspective: Potential Intervention For Mitigate...mentioning
confidence: 99%
“…PPARα and PPARγ, which are members of an important class of nuclear hormone receptors (PPARs), are additional targets of endocannabinoids. 103,104 Although the data are more significant for some cannabinoids, such as N-oleoylethanolamine (OEA) and Npalmitoylethanolamine (PEA), neuroprotective, antiinflammatory and analgesic effects have been considered to be mediated, in part, by their activation of PPARs. However, there are a myriad of factors influencing the interactions between cannabinoids and PPARs that need to be elucidated.…”
Section: Additional Pharmacological Targets Involved With Cannabinoid...mentioning
confidence: 99%
“…Future research will confirm if this can also be the case in other neuropsychiatric conditions. Moreover, in relation with neuropsychiatric disorders, Jung et al (2020) reviewed the relevant literature on the potential link between cannabinoids (especially cannabidiol), omega‐3 fatty acids, and peroxisome proliferator‐activated receptors in the regulation of neuropsychiatric alterations. Specifically, they propose how this relationship might be involved in the modulation of dopaminergic abnormalities often associated with neuropsychiatric symptoms.…”
Section: Cannabinoid Signalling In Diseasementioning
confidence: 99%